Confucius’ Ontological Ethics - Steiris, Georgios (Conatus - Journal of Philosophy, 2023)
Confucius associates the good and the beautiful. Li (translated variously as “ritual propriety,” “ritual,” “etiquette,” or “propriety”) embodies the entire spectrum of interaction with humans, nature, and even material objects. I argue that Confucius attempts to introduce an ethical ontology, not of “what,” but of “the way.” The “way” of reality becomes known with the deliberate participation to the Dao. In other words, through interaction. The way people co-exist demonstrates the rationality of the associations of living and functioning together. Li, as an aesthetic-moral principle, embodies the entire spectrum of one’s interaction with humans, nature, and even material objects. Li is a constitutive element of Confucian ethics and politics, highlighting the importance of beauty, and not only goodness, in human action. The worthiness of human action is judged both aesthetically and morally. Moreover, I hold that Confucius’ ethical ontology is not an ontology of “whatness” but of “howness,” according to the Dao, since Confucius primary concern was not to define the Dao, but to restore the Dao of the ancient sage-kings. The morality of the action is dependent on the way it is performed, according to the mandates of the Dao.